PERANCANGAN APLIKASI ENKRIPSI DAN DEKRIPSI FILE BERBASIS WEB - Pas Mahyu Akhirianto; Anita B. Wandanaya; Opan Mustopah (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2016)
In the development of technology that is so advanced today, especially in the field of communication and information, maintaining privacy is something that absolutely must be done for each individual. Rapoport (in Soesilo, 1998) defines privacy as an ability to control the interaction, the ability to acquire options and the ability to achieve the desired interaction. Nowadays, a lot of things that can be done by using the internet, such as selling, social interacting through social media (Social Media) such as Facebook, learn, or just read the news through the portal of electronic media, and so forth. Most of the activities that can be done on the internet, requires personal data of its users, where the issue of privacy is of onsiderableconcern. As the development of information and communication technology in this case the Internet, the technology used to protect all personal data users also grown and will continue to evolve into more sophisticated. For this reason the author took the initiative to create a Endesapp application program, which aims to facilitate a person or agency who frequently exchange data in the form of files through the Internet. With so security in maintaining personal data even be increased as well as the possibility of the spread of sensitive data has been poor. In this study, the method used is to design programs shaped application file encryption and decryption web-based cryptographic techniques to the type of algorithm that is supported is 3DES ( Triple DES ) , AES - 128 ( Advanced encyption Standard) , AES - 192 and AES - 256.